Analisis Pembentukan Identitas Diri Tokoh Utama dalam Novel Sesuk Karya Tere Liye Berhubungan dengan Faktor Perasaan dan Implikasi Pada Pembelajaran Sastra di SMA - Feny Hariany; Lazarus Linarto; Misnawati Misnawati; Alifiah Nurachmana; Ruliyani Ruliyani; Jauharratun Naimah (Universitas Palan, 2023)
This research aims to: (1) describe the formation of the main character's self-identity in the novel Sesuk by Tere Liye in relation to feelings factors, (2) Describe the implications of the main character in the novel Sesuk by Tere Liye in Literature Learning in High School. The data source in this research is the novel Sesuk with Structural theory. The research method used is a description method with a qualitative description approach. A qualitative description approach is used to describe the formation of the main character's self-identity in the novel and describe the implications for literature learning in high school. The results of this research: (1) Analysis of the formation of the main character Sesuk's self-identity in the novel Sesuk by Tere Liye based on the factor of feeling happy. In the novel Sesuk by Tere Liye, the feelings that emerge are sad, happy, happy and moved. (2) implications for literature learning in high school in accordance with Basic Competencies (KD), Learning Materials and learning activities related to novels for class XII Indonesian language competency knowledge and skills.